Speech Enhancement based on 2D Gabor Filters for Arabic Phoneme Spoken by Malay Speakers - Abd Almisreb, Ali; Md Tahir, Nooritawati; Farid Abidin, Ahmad; Md Din, Norashidah (International Journal of Engineering and Technology, 2018)
In this paper, a speech enhancement method using 2D Gabor filter is proposed. The proposed filter is used to enhance Arabic phoneme speech signals that have been recorded under control environment namely indoor room recording. All the phoneme signals are spoken by Malay speakers and considered as non-native Arabic speakers. Firstly, corrupted speech signals by noise must be enhanced before further processing. The effectiveness of the suggested approach is evaluated in compare with Wiener filter. It is proven that the proposed 2D Gabor filters performed appropriately for speech enhancement purpose at different wavelengths.